2023
DOI: 10.1021/acsaenm.3c00326
|View full text |Cite
|
Sign up to set email alerts
|

Trace Detection of Ciprofloxacin in Milk by Label-Free Raman Enhancement using Two-Dimensional Magnesiochromite

Anyesha Chakraborty,
Partha Kumbhakar,
Preeti L. Mahapatra
et al.

Abstract: Antibiotic resistance and adverse reactions in humans can be avoided by detecting antibiotics early in the milk supply chain. To meet the demand, we developed a flexible and simple optical sensing method based on a non-van der Waals two-dimensional (2D) metal oxide, 2D-magnesiochromite (2D-MgCr2O4). We used a rapid, label-free Raman enhancement mechanism for antibiotic detection. The Raman spectral mapping method has also been used to quickly identify traces of antibiotics in food products. Here, we have used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The thickness of the 2D flakes can be determined by the AFM images obtained from Figure d. Based on the histogram present in the inset, it is evident that the thickness of all flakes falls within the range of 1–10 nm, thereby meeting the requisite criteria for the formation of a 2D structure . Furthermore, it is observed that the majority of the flakes exhibit a thickness ranging from 3 to 5 nm, which confirms the formation of few-layered 2D CoTe 2 .…”
Section: Resultsmentioning
confidence: 92%
“…The thickness of the 2D flakes can be determined by the AFM images obtained from Figure d. Based on the histogram present in the inset, it is evident that the thickness of all flakes falls within the range of 1–10 nm, thereby meeting the requisite criteria for the formation of a 2D structure . Furthermore, it is observed that the majority of the flakes exhibit a thickness ranging from 3 to 5 nm, which confirms the formation of few-layered 2D CoTe 2 .…”
Section: Resultsmentioning
confidence: 92%
“…For the exfoliated T-silicate, the potential is −30 mV, which suggests a negative charge on the exfoliated sheets. Zeta potentials of graphene, 27 hBN, 28 MoS 2 , 29 2D black phosphorus, 27 2D spinel oxide, 30 and 2D layered silicates such as mica 31 and biotite 32 were compared with those of non-layered 2D T-silicates reported in this work.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that 2D silicates have higher stiffness values [45] than black phosphorus [46], silicene [47], and WSe 2 but lower than MoS 2 [48], graphene [49], and hBN [50]. The zeta potential values (stability in suspension and charge) are negative for 2D silicates [51,52] and larger than the corresponding values for the majority of 2D materials [53][54][55][56], as shown in figure 2(d). The magnetic property chart in figure 2(e) indicates that natural silicates in 2D configurations are predominantly paramagnetic, but ferromagnetic (FM) behavior is possible if combined with appropriate elements [57].…”
Section: Comparison Of Characteristics With Other 2d Materialsmentioning
confidence: 87%